ظاهرة التوازي في قصائد شوقي الوطنية: دراسة وصفية تحليلية (The Phenomenon of Parallelism in Shawky's Nationalistic Poems: A Descriptive Analytical Study) - بن محمد شريف, محمد حفيز; إبراهيم أحمد حسين, نصر الدين (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
يتناول هذا البحث تحليل ظاهرة التوازي في قصائد شوقي الوطنية، بمعنى أن هذه الخاصية الفنية أهم عنصر لتوظيف الموسيقى الداخلية، في حين أنها ظاهرة تحتوي على ثروة دلالية كأبرز وسيلة للتعبير عن تجربة الشاعر وانفعالاته. اعتمادا على المنهج الوصفي والتحليل؛ يهدف هذا المقال إلى الكشف عن السمات الجماليات إيقاعيا ودلاليا، المتعلقة بأبرز أنماط التوازي: الصوتي والتركيبي والدلالي، التي استثمرها شوقي في الأشعار التي عبر فيها عن قضايا وطنه. وتبرز أهمية هذه الدراسة في أنها تسلط الضوء على أشكال بلاغية: الجناس، والترصيع، والتقسيم، والطباق، والمقابلة، والعكس والتبديل وغيرها مما له أكبر تأثير في تشكيل ظاهرة التوازي. وخلص البحث إلى أن الشاعر توسل في تشكيل البنية الإيقاعية بإبداعاته الفنية في هذه الظاهرة؛ لإثراء النغمة الموسيقية التي تؤثر في عواطف المتلقين، والتي كانت أيضا صدى لانفعالات الشاعر وأحاسيسه. الكلمات المفتاحية: ظاهرة التوازي، القصائد الوطنية، الأشكال البلاغية، البنية الإيقاعية، ثروة دلالية. Abstract This research analyses the phenomenon of parallelism in Shawky's nationalist poems, in the sense of that this is the most important element for employing the internal rhyme, while it is a phenomenon that carries semantic richness, as it is considered one of the most prominent ways to express the poet’s experiences and emotions. Relying on the descriptive analytical approach, this article aims to reveal the rhythmic and semantic aesthetic features related to the most remarkable patterns of parallelism: phonemic, syntactic, and semantic, that Shawki used it in his poems, through which he expressed the issues of his homeland. The importance of this study is evident in that it focuses on rhetorical forms: Alliteration (al Jinas), Homoioptoton (al Tarsi'), Antithesis (al Tibaq, al Muqabala), Antimetabole (al 'Aks), etc., which has the greatest impact on shaping the phenomenon of parallelism. The research concluded that the poet could form the rhythmic structure with his artistic creations in this phenomenon, it enriches the musical tone that influences the emotions of the recipients, which was also as the echo of the poet’s emotions and feelings. Keywords: Phenomenon of parallelism, Nationalistic poems, Rhetorical forms, Rhythmic structure, Semantic richness.